Titin and desmosomal genes in the natural history of arrhythmogenic right ventricular cardiomyopathy - Brun, Francesca (J Med Genet, 2014)
BACKGROUND: Genotype-phenotype correlations are poorly characterized in arrhythmogenic right ventricular cardiomyopathy (ARVC). We investigated whether carriers of rare variants in desmosomal genes (DC) and titin gene (TTN) display different phenotypes and clinical outcomes, when compared to non-carriers (NT-ND). METHODS AND RESULTS: Thirty-nine ARVC families (173 subjects, 67 affected) with extensive follow up (mean 9 years), prospectively enrolled in the International Familial Cardiomyopathy Registry since 1991, were screened for rare variants in TTN and desmosomal genes (DSP, PKP2, DSG2, DSC2). Multiple clinical and outcome variables were compared between 3 genetic groups (TTN, DC, NT-ND) to define genotype-phenotype associations. Of the 39 ARVC families, 13% (5/39) carried TTN rare variants (11 affected subjects), 13% (5/39) DC (8 affected), while 74% (29/39) were NT-ND (48 affected). Compared to NT-ND, DC had a higher prevalence of inverted T waves in V2-3 (75% vs. 31%, p=0.004), while TTN had more supraventricular arrhythmias (46% vs. 13%, p=0.013) and conduction disease (64% vs. 6% p<0.001). Compared to the NT-ND group, the DC group experienced a worse prognosis (67% vs. 11%, p=0.03) and exhibited a lower survival free from death or heart transplant (59% vs. 95% at 30 years, and 31% vs. 89% at 50 years, HR 9.66, p=0.006), while the TTN group showed an intermediate survival curve (HR 4.26, p=0.037). CONCLUSIONS: TTN carriers display distinct phenotypic characteristics including a greater risk for supraventricular arrhythmias and conduction disease. Conversely, DC are characterized by negative T waves in anterior leads, severe prognosis, high mortality and morbidity.